Impact Of Social Media, Customer Experience And Servicescape On The Revisit Intention In Marine Tourism - Yaumil Atia A. A. Omar; Haris Maupa; Haeriah Hakim (Program Pascasarjana STIE Amkop Makassar, 2023)
This study aims to determine the impact of social media, customer experience and servicespae on revisit intention in marine tourism Akkarena Beach, Makassar. Research data was gathered via conducting interviews and disseminating questionnaires. The approach for sample selection was based on the Slovin formula, which resulted in a sample of 96 respondents who had frequented Akkarena Beach as a marine tourism destination and were active on social media platforms. The analysis technique used is Multiple Regression to prove the research hypothesis. The results show that the T test (partial) on the social media, customer experience and servicescape each have a positive and significant impact on revisit intention. By F test (silmultaneous) on social media, customer experience and servicescape variables have a positive and significant impact on revisit intention. Keywords: Social Media, Customer Experience, Servicescape, Revisit Intention.